Implant Complications After Magnetically Controlled Growing Rods for Early Onset Scoliosis: A Multicenter Retrospective Review. Issue 8 (December 2017) - Choi, Edmund; Yaszay, Burt; Mundis, Gregory; Hosseini, Pooria; Pawelek, Jeff; Alanay, Ahmet; Berk, Haluk; Cheung, Kenneth; Demirkiran, Gokhan; Ferguson, John; Greggi, Tiziana; Helenius, Ilkka; et al.
Abstract : Background: Traditional growing rods have a reported wound and implant complication rate as high as 58%. It is unclear whether the use of magnetically controlled growing rods (MCGR) will affect this rate. This study was performed to characterize surgical complications following MCGR in early onset scoliosis. Methods: A multicenter retrospective review of MCGR cases was performed. Inclusion criteria were: (1) diagnosis of early onset scoliosis of any etiology; (2) 10 years and younger at time of index surgery; (3) preoperative major curve size >30 degrees; (4) preoperative thoracic spine height <22 cm. Complications were categorized as wound related and instrumentation related. Complications were also classified as early (<6 mo from index surgery) versus late (>6 mo). Distraction technique and interval of distraction was surgeon preference without standardization across sites. Results: Fifty-four MCGR patients met inclusion criteria. There were 30 primary and 24 conversion procedures. Mean age at initial surgery was 7.3 years (range, 2.4 to 11 y), and mean duration of follow-up 19.4 months. Twenty-one (38.8%) of 54 patients had at least 1 complication. Fifteen (27.8%) had at least 1 revision surgery. Six (11.1%) had broken rods (2 to 4.5 and 4 to 5.5 mm rods); two 5.5 mm rods failed early (4 mo) and 4 late (mean=14.5 mo). Six (11.1%) patients experienced 1 episode of lack or loss of lengthening, of which 4 patients subsequently lengthened. Seven patients (13.0%) had either proximal or distal fixation-related complication at average of 8.4 months. Two patients (3.7%) had infections requiring incision and drainage; 1 early (2 wk) with wound drainage and 1 late (8 mo). The late case required removal of one of the dual rods. Conclusions: This study shows that compared with traditional growing rods, MCGR has a lower infection rate (3.7% vs. 11.1%). MCGR does not appear to prevent common implant-related complications such as rod or foundation failure. The long-term implication remains to be determined. Level of Evidence: Level IV.